The Influence of Product Quality and Promotion on Purchasing Decisions at a used car company - Hestin Septiana Wahyu Utami; Boy Suzanto (LPPM STMIK Mardira Indonesia, 2024)
The purchasing choice significantly impacts marketing and can be influenced by various aspects, including product quality, promotions, and other variables. This study examines the impact of product quality, advertising, and buying decisions on used automobile sales at a particular used car dealership. This study aims to assess and evaluate the influence of product quality and promotional activities on consumer purchasing choices within the selected used automobile firm. This study utilizes descriptive and confirmatory analysis techniques with a sample size of 97 participants. The chosen analytical technique is path analysis, and the software utilized is SPSS version 16. The study's findings indicate that, according to path analysis, the variable of product quality (X1) exerts a direct influence of 33.8%, an indirect influence through its association with promotions of 13.4%, and an overall influence of 47.2%. The promotion variable (X2) has a direct impact of 7.2%, an indirect impact through its correlation with product quality of 13.4%, and a total impact of 20.6%. The combined impact of the variables product quality (X1) and promotion (X2) on the purchase decision (Y) amounts to 67.8%, with the remaining 32.2% being ascribed to unexamined variables in this study. The study's findings indicate that it is advisable to prioritize product quality and promotions to improve buying decisions.